1995
DOI: 10.1021/jm00014a026
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Inhibitors of the Gastric (H+/K+)-ATPase. 4. Identification of an Inhibitor with an Intermediate Duration of Action

Abstract: 3-Acyl-4-(arylamino)quinolines were previously identified as gastric (H+/K+)-ATPase inhibitors, and clinical efficacy has been demonstrated for compound 3 (SK&F 96067). In the present study the further structure-activity relationship of this series is developed. Only a limited range of substituents are tolerated on the N-aryl ring or the 6- and 7-positions of the quinoline, and although hydroxylated derivatives were identified possessing markedly greater affinity for the enzyme, none of these proved to have ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Much of the earlier work performed on 1a and 1b was based on this disconnection. The compounds were originally prepared within the Medicinal Chemistry research programme using several routes, the most promising one of which is shown in Scheme 1. , Although this classical route was amenable to the large-scale preparation of 1a , the requirement for either aluminium trichloride or boron tribromide for the demethylation of the 8-methoxyquinoline 4a to give the somewhat unstable 8-hydroxy analogue 4b and poor yields for the alkylation of the latter to give the final product 1b necessitated the acquisition of alternative methodology for the preparation of 1b . The aspects concerning the evolution of an efficient conversion of 1a to 1b are dealt with later in the paper.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Much of the earlier work performed on 1a and 1b was based on this disconnection. The compounds were originally prepared within the Medicinal Chemistry research programme using several routes, the most promising one of which is shown in Scheme 1. , Although this classical route was amenable to the large-scale preparation of 1a , the requirement for either aluminium trichloride or boron tribromide for the demethylation of the 8-methoxyquinoline 4a to give the somewhat unstable 8-hydroxy analogue 4b and poor yields for the alkylation of the latter to give the final product 1b necessitated the acquisition of alternative methodology for the preparation of 1b . The aspects concerning the evolution of an efficient conversion of 1a to 1b are dealt with later in the paper.…”
Section: Resultsmentioning
confidence: 99%
“…The final hydroxyethylation stage to form 1b was previously performed by using 2-bromoethanol in the presence of potassium tert -butoxide, giving yields of ∼30% . Extensive development work facilitated the evolution of a superior process, which involved the use of ethylene carbonate in the presence of either K 2 CO 3 or DABCO in refluxing 2-propanol and afforded 1b in 60−80% yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…other cysteine residues of the proton pump through covalent S-S bond formation, or they could behave as reversible potassium channel antagonists [51].…”
Section: The H + /K + Atpase Enzyme or The Proton Pumpmentioning
confidence: 99%
“…4‐Hydroxyquinolines (equal to 4‐oxo‐1,4‐dihydroquinolines) are the key synthetic precursors for anticancer , antimalarial , antidiabetic , antiviral agents, and reversible (H + /K + ) ATPase inhibitors . N ‐(3‐Cyano‐7‐ethoxy‐4‐oxo‐1,4‐dihydroquinolin‐6‐yl)acetamide ( 1 ) (Fig.…”
Section: Introductionmentioning
confidence: 99%